Infrared thermographic evaluation of rise in temperature with conventional versus trephine drills - Siddharth Gupta; Ambika Shrivastava Gupta; G S Chandu; Shilpa Jain (Wolters Kluwer Medknow Publications, 2021)
Aim: To compare the rise in temperature using trephines over conventional ones during bone site preparation. Setting and Design: An-vitro, evaluative study Materials and Methods: Twenty implant sites were prepared using pilot drill up to depth of 10 mm on bovine femoral bone. In first part, no irrigation was used. Five sites were prepared using conventional drill of 2.8 mm, and other five were prepared with help of trephine drills. On completion of each drill, infrared thermometer was used to measure temperature on both the drill tip and the shaft. The same procedure was repeated with bone immersed in saline. Statistical Analysis Used: Student t test was used to evaluate the significance of difference. Result: Study showed that the temperature rise at drill tip was significantly higher for trephine drill (52.98 ± 1.67 °C) than conventional drills (48.20 ± 0.67 °C), however the temperature difference in trephine and conventional drills was statistically insignificant. Conclusion: The temperature increase was more distributed in conventional drills than trephine. Copious irrigation is thus mandatory for trephine drills. Intermittent drilling is preferred with conventional drills.